Youth in Agriculture: Role of Government Initiatives - Rani, Anshu; Roy, Pinaki (Journal of Agricultural Extension Management, 2018)
Youth are the building blocks of a nation. The role of the youth in nation-building occupies the central position. Development of youth determines the development of the community and the country as a whole. The socio-economic development and prosperity of the rural areas depend upon the potential youth of the country, as the rural youth have abilities to orient themselves to go along with the mainstream of the development process. India both before and after independence has witnessed emergence of youth as a potential force and to reckon with it, the involvement of youth in national developmental activities is necessary. It was felt significantly relevant because of their boundless energy and innate idealism, which could give a positive direction in improving the quality of life. To harness the potential of youth and to take the benefit of demographic dividend holistically, Government of India has announced multifarious schemes. These schemes are based on the principles of social inclusion, gender equality and sustainable development of rural areas. The difference in basic amenities, communication, health and education facilities between villages and urban areas attract youth towards the cities.